Operational Evaluation of Part-Time Shoulder Use for Interstate 476 in the State of Pennsylvania - Sean Coffey; Seri Park (Advances in Civil Engineering)
Part-time shoulder use (PTSU) is a capacity-adding strategy that utilized the shoulder temporarily during the peak commuting period and is used sporadically throughout the United States of America (USA). This strategy aids in addressing a transportation-related issue for major metropolitan areas. Around major metropolitan areas, the land availability is limited due to high population counts, which makes widening roadways for growing populations complex and expensive. Many countries are looking at methods that better utilize the transportation infrastructure currently constructed before widening the roadway. PTSU provides a possible solution to this problem, and this research aims to evaluate the operational benefits of PTSU using a case study based in the state of Pennsylvania. Interstate 476 (I-476), in the Philadelphia, Pennsylvania, metropolitan area is a prime candidate for PTSU. This four-lane highway has peak directional volumes of around 4,700 vehicles per hour in particular sections during the morning commuting period. I-476 is a major commuting route for the region, and the additional capacity during the commuting periods would greatly improve the flow of the surrounding network. This analysis was completed using a Vissim model simulating the 7 AM to 9 AM commuting period. A variety of PTSU scenarios were analyzed including (1) general purpose PTSU lane, (2) passenger cars only PTSU lane, (3) heavy trucks only PTSU lane, and (4) general purpose PTSU lane where additional traffic is induced. Overall, this study determined that PTSU could significantly decrease the travel time on I-476, regardless of vehicle type restrictions, and could provide a more stable traffic density throughout the I-476 network. This research provides additional insight into the effects of vehicle type restrictions on the effectiveness of PTSU and further strengthens the understanding of the operational benefit of PTSU.